An Interactive relationship between linguistic techniques and cognitive cities - Ahmed Mahmoud, Ragheb Ahmed (2013)
Abstract: This study deals with the rationale that should be built by the machine translation of any natural language, with the application of these principles to the reality of the Arabic language. Any successful mechanism for translation should not have limited reliance on mere lexical replacements or anything equivalent to that of reclining on a level surface for the input language. The transition processes in the automatic translation to a deep interlocking structure of the language involves many difficulties and challenges, but the results will be more positive in the results of those translations. The research is faced with databases of machine translation with a perception that applied treatment of the language will overlap in these rules, and through exposure to analyze the levels of linguistic voice, morphological, syntactic, semantic, and then move to the perception and reality applied to the Arabic network implications and try to employ these advances to improve the performance of the output of machine translation to the satisfaction of language users and scientists.